Expression of cholinesterases and their anchoring proteins in rat heart - Kilianova, Zuzana; Ciznarova, Natalia; Szmicsekova, Kristina; Slobodova, Lubica; Hrabovska, Anna (Canadian journal of physiology and pharmacology, 2020)
Acetylcholine (ACh)-mediated vagal transmission as well as nonneuronal ACh release are considered cardioprotective in pathological situations with increased sympathetic drive such as ischemia-reperfusion and cardiac remodeling. ACh action is terminated by hydrolysis by the cholinesterases (ChEs), acetylcholinesterase, and butyrylcholinesterase. Both ChEs exist in multiple molecular variants either soluble or anchored by specific anchoring proteins like collagen Q (ColQ) anchoring protein and proline-rich membrane anchoring protein (PRiMA). Here we assessed the expression of specific ChE molecular forms in different heart compartments using RT-qPCR. We show that both ChEs are expressed in all heart compartments but display different expression patterns. The acetylcholinesterase-T variant together with PRiMA and ColQ is predominantly expressed in rat atria. Butylcholinesterase is found in all heart compartments and is accompanied by both PRiMA and ColQ anchors. Its expression in the ventricular system suggests involvement in the nonneuronal cholinergic system. Additionally, two PRiMA variants are detected throughout the rat heart.
Keywords: Membrane Proteins; collagen Q anchoring protein; proteiny nervové tkáně; butyrylcholinestérase; butyrylcholinesterase; Nerve Tissue Proteins; acetylcholin; acétylcholinestérase; « proline-rich membrane anchoring protein »; acetylcholine; krysa rodu Rattus; acetylcholinesterase; kolagen; zvířata; « collagen Q anchoring protein »; GPI-Linked Proteins; Collagen; potkani Wistar; Acetylcholine; Isoenzymes; Rats, Wistar; butyrylcholinesterasa; Male; izoenzymy; Acetylcholinesterase; stanovení celkové genové exprese; Real-Time Polymerase Chain Reaction; Rats; membránové proteiny; myokard; Animals; GPI-vázané proteiny; Gene Expression Profiling; Myocardium; mužské pohlaví; proline-rich membrane anchoring protein; Butyrylcholinesterase; acetylcholinesterasa; kvantitativní polymerázová řetězová reakce; acétylcholine